Progettare insieme: Processi partecipativi a contrasto dell’homelessness tra antropologia e design - Porcellana, Valentina; Campagnaro, Cristian (Antropologia Pubblica, 2019)
For several years now, we have been combining methods and tools belong-ing to both anthropology and design, with the aim of testing out innovative solutions to homelessness. From the beginning of our interdisciplinary research in 2009 in several Italian cities, it became evident homelessness comprises far more complex circumstances than just the lack of a home. We have chosen not to be simple observers of a situation of services deterioration but to be agents of change, despite all the ethical and method-ological risks that this choice involves. The best way to try to understand something is to change it. In this sense, for us, entering the homelessness services system means to understand the workings of the institution from within and to work with all players to fully meet people’s needs. The change we experienced is the result of an incremental and participatory transformational approach that fosters a positive outlook and moves towards the right to the dignity related to home and aspirations.